Characterization of Acute Leukemia Types and Subtypes using Flowcytometer at a Tertiary care Hospital of South Punjab - Rubab, Zill-e (International Journal of Pathology, 2023)
Introduction: Acute leukaemia is a common disorder among children having age 2 to 5 years and fever, progressive pallor, fatigue, bleeding and easy bruising are common complaints of patients. Flow cytometric immunophenotyping is the test that is used for the diagnosis of acute leukaemia and its sub-classification. This susceptible and specific test gives an insight into bone marrow cell maturation and shows multidimensional radar plots.Objective: To characterize acute leukaemia, its types and subtypes using a flow cytometer in childrenMaterial and Methods: This descriptive Cross Sectional study was conducted at the department of Hematology in Children's Hospital and Institute of Child Health, Multan for a duration of one year from 1st February 2021 to 30th January 2022. It was performed after written informed consent in the Pathology department of Children’s Hospital & the Institute of Child Health Multan. Immunophenotyping was performed using a flow cytometer of all study participants.Results: A total of ninety-three children aged 1-15 years with acute leukaemia on peripheral blood or bone marrow aspirate smears were enrolled in the current study. We analyzed that fever, pallor and body aches were the common (80%) clinical presentations in our patients. The median age of study participants was 7.1 ± 3.98 years. Male to female ratio was 2.4:1. Majority of patients were found to have pre-B cell ALL (73.1%) followed by T cell ALL (15%), AML (7.5%) and phenotypic acute leleukaemia4.3%). We divide our patients into three age groups. Pre B cell ALL was commonly found in age group 1-5 years, T cell ALL in 10-15 years and AML in 5-10 years. CD 10 marker showed maximum positivity in pre-B cell ALL. Among B cell markers CD 79a showed the highest positivity (96.7%) followed by CD19 (92.1%) while in T cell ALL 100% positivity was seen in CD 3.Conclusion: Flowcytometer is an essential tool for the characterization of acute leukaemia, its types and subtypes